Effect Of A Physical Activity And HealthRelated Quality Of Life Among Older Adults Living In Makkah City Saudi Arabia 2025 (The Review of Diabetic Studies, 2025)
BackgroundOlder adults are a rapidly growing segment of the Saudi Arabia. population. Mobility problems that lead to further disability can be addressed through physical activity interventions. Quality of life outcome results are reported from a large trial of physical activity for sedentary older adults at risk for mobility disability. Physical activity can improve health-related quality of life (HRQoL) in older adult; also the effect of physical activity on quality of life is unclear among the Saudi adult population. Physical activity is associated with health-related quality of life (HRQL) in clinical populations, but less is known whether this relationship exists in older men and women who are healthy, people aged 85 years and over are the fastest-growing group, and the proportion of these “oldest old” is expected to triple between now and year 2030. Continued good health of the elderly population is a major challenge to public health.  Aim of the study: To assess the effect of a physical activity and health-related quality of life among Older Adults living in Makah city Saudi Arabia 2025 Methods: cross-sectional descriptive study conducted at among Older Adults, age above the 50 years among visitors of walking tracks/fitness centres/gyms and governmental hospitals in Makkah city  and contacted to participate in an 8-month follow-up. Individuals completed a battery of questionnaires assessing activities of daily living, dependence on medicines and medical aids, energy and fatigue, mobility, pain and discomfort, sleep and rest, Work capacity, dependence on medicines and medical aids, our total of 300 eligible participated in this study start from March to September.  Results most of the participants with their family were (69.0%) follow by alone were (31.0%), regarding the location the majority of them were Gym/Walking tracks were (52.0%) while hospital visitors were (26.0%) while malls were (22.0%), regarding body mass index (BMI) the majority of participant normal were (42.0%) followed by overweight were (37.0%( while obese were (21.0%) Conclusion: The article reinforces how physical activity contributes towards each dimension of HRQoL. Physical inactivity is a growing public health challenge in Saudi Arabia, affecting all age groups, also especially the elderly. Our findings support the role of self-efficacy in the relationship between physical activity and QOL as well as an expanded QOL model including both health status indicators and global QOL